2020
DOI: 10.51791/njap.v47i1.193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unconventional marinades on beef quality

Abstract: There is consumer's preference for tender meat. The use of tenderizers to soften meat helps to reduce nutrient losses due to prolonged cooking. This study was conducted to compare the effects of four unconventional marinades (Pawpaw leaves extract, Lime-juice, and Carbonated drinks and distilled water) on the quality of beef. One thousand five hundred grams (1500 g) of beef excised from the thigh muscle was cut into twelve whole pieces of similar sizes and were randomly distributed into four experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These samples possessed a delicate, juicy consistency, a clear appearance in the cut, and a pleasant taste and aroma. Scientific articles (Suárez et al, 2021;Trabelsi et al, 2018;Obajuluwa et al, 2020;Jung et al, 2018) presents several experimental studies concerning the use of marinades based on olive, corn, soybean, and peanut oils in various combinations and ratios. We performed several experiments and found that some samples did not have a juicy consistency and an unpleasant taste and aroma (a mixture of corn and soybean oils).…”
Section: Resultsmentioning
confidence: 99%
“…These samples possessed a delicate, juicy consistency, a clear appearance in the cut, and a pleasant taste and aroma. Scientific articles (Suárez et al, 2021;Trabelsi et al, 2018;Obajuluwa et al, 2020;Jung et al, 2018) presents several experimental studies concerning the use of marinades based on olive, corn, soybean, and peanut oils in various combinations and ratios. We performed several experiments and found that some samples did not have a juicy consistency and an unpleasant taste and aroma (a mixture of corn and soybean oils).…”
Section: Resultsmentioning
confidence: 99%